Culture and the self-identity of women entrepreneurs in a developing country - Mazonde, Nomusa Benita (My University, 2016)
The purpose of this research is to understand female entrepreneurship from the perspective of the female entrepreneurs themselves. Much of the literature in this field has been in the context of developed countries, and relatively little research has explored the entrepreneurial experiences of women entrepreneurs in developing countries. The study followed the interpretive approach utilising a social constructivist theoretical perspective, which sought to understand female entrepreneurs in terms of their subjectively constructed reality. Forty-three purposively selected female entrepreneurs, whose businesses had transitioned from the informal economy to the formal economy, were both observed and interviewed in depth. The data were analysed using principles of constant comparison and coding, then used to formulate theoretical propositions of female entrepreneurship. During the coding process, care was taken to safeguard the language and voice of the interviewees from the raw data through to the contribution to theory. This study reveals that female entrepreneurs’ initial identities evolve through unshackling themselves from the imposed patriarchal structures into new identities. Their initial identities were disenfranchised and shaped by their historical context. The female entrepreneurs engage in a process of balancing through their own agency; this shift is essential to their functioning as successful entrepreneurs. The circumstances and motivation for these female entrepreneurs typified the intentions of other female entrepreneurs; they were compelled to juggle their family considerations with the demands of their entrepreneurial activities. Notably, they relied on their personal expertise, and augmented their personal financial resources with bootstrapping instead of relying on debt. In addition, the study indicates that family, religion, and community are the driving forces sustaining the commitment to entrepreneurship amongst these women; it is not profit alone, although income is important to sustain those who rely on their support. The results indicate a strong association between historical context - understood in terms of cultural traditions - and female entrepreneurial activities. Culture and family can either be a constraint on, or an enabler of female entrepreneurship in a developing country context. In summary, the study may be helpful to current and future entrepreneurs as it examined the personal lived experiences as well as the contextual influences of these courageous women.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, March 31st 2016
Keywords: Women-owned business enterprises--Developing countries; Businesswomen--Developing countries; Entrepreneurship--Developing countries